Repair layer for water erosion damage of last-stage blade of steam turbine and preparation method of repair layer

By using laser cladding technology to form a restoration layer and a transition layer on the final stage of the turbine, the problem of shortening the blade life caused by water erosion damage is solved, and the high hardness, high toughness and good water erosion resistance of the repair layer are achieved, extending the service life of the blade and improving operating reliability.

CN119571307APending Publication Date: 2025-03-07SHANGHAI HUADIAN FENGXIAN THERMAL POWER CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411538206.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The final stage blades of the turbine are susceptible to water corrosion damage during work, resulting in a shortening of the service life of the blade. The existing repair methods such as supersonic flame spraying and brazing of the Sitali alloy sheet have problems such as low bond strength and insufficient water corrosion resistance.

Method used

Laser cladding technology is used to form a restoration layer and a transition layer in the area to be repaired in the final blade. The restoration layer is made of 20% tough phase and 80% nickel-chromium-based alloy powder, and the transition layer is made of 20% tough phase and 80% iron-based alloy powder. The stability and reliability of the restoration layer are improved through metallurgical combination.

Benefits of technology

The repair layer has high hardness, high toughness, good fatigue resistance and strong water corrosion resistance, extending the service life of the last-stage blade of the turbine, reducing maintenance costs, and improving the operating reliability of the turbine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571307A_ABST
    Figure CN119571307A_ABST
Patent Text Reader

Abstract

The invention relates to a repair layer for water erosion damage of a last-stage blade of a steam turbine and a preparation method of the repair layer, a to-be-repaired area of the last-stage blade is formed by laser cladding, the repair layer comprises at least one recovery layer, and materials needed by the laser cladding recovery layer comprise 20% of a tough phase and 80% of nickel-chromium-based alloy powder. The nickel-chromium-based alloy powder comprises the following elements in percentage by mass: 0.03-0.08% of C, 30.45-30.55% of Cr, 0.15-0.25% of Si, 8.15-8.25% of Fe, 1.45-1.55% of Mo and the balance of Ni, when laser cladding is used for preparing the recovery layer, a fine hard phase in the recovery layer can play a dispersion strengthening role, Ni and Cr can generate a (Ni, Cr) solid solution under the action of high temperature to play a solid solution strengthening role, and the recovery layer can be used for preparing the recovery layer. And the separated carbide is used as a nucleation center to promote the formation of secondary dendritic crystals, so that crystal grains generated in a recovery layer are effectively refined, and the fine crystal strengthening effect is achieved. Therefore, the repair layer containing the recovery layer has the advantages of being high in hardness and toughness, good in fatigue resistance, high in water erosion resistance and the like, the service life of the last-stage blade of the steam turbine is effectively prolonged, and economical efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material repair, and in particular to a repair layer for water erosion damage of a last-stage blade of a steam turbine and a preparation method thereof. Background Art

[0002] A steam turbine is a rotary fluid power machine that converts the thermal energy of steam or gas into mechanical energy in large coal-fired and gas-fired units. The blades of a steam turbine are the "heart" of the turbine and are extremely important parts of the turbine. When the turbine is working, high-temperature and high-pressure steam acts on the steam inlet edge of the blade. The high-temperature steam liquefies and produces water droplets when it encounters the low-temperature blade. Over time, the steam inlet edge of the blade is easily eroded by water droplets, which affects the service life of the blade. In addition to severe water erosion on the steam inlet edge, the steam outlet edge of the last-stage moving blades of large coal-fired and gas-fired units also has varying degrees of water erosion. As large coal-fired and gas-fired units gradually implement deep peak regulation, the last-stage blades of the steam turbine units are forced to operate under low-load conditions. The root of the last-stage blade has a large negative reaction degree, which generates backflow at the root of the last-stage moving blade. The backflow carries water droplets and hits the steam outlet edge of the blade to form water erosion damage. Water erosion damage to the last-stage blades of a steam turbine will cause the aerodynamic performance of the turbine blade cascade to deteriorate. The uneven edges left by water erosion of the blades are prone to stress concentration, increasing the blade shape loss and causing the cross-sectional area of ​​the blade root to decrease, thus weakening the blade strength and increasing the risk of last-stage blade breakage. In view of this, timely repair and protection of the last-stage blades with severe water erosion will prevent the last-stage blades from breaking and ensure the safe operation of the steam turbine unit.

[0003] The traditional method of repairing the water erosion of the last-stage blade is to use supersonic flame spraying to atomize the molten spray material through a high-speed airflow and spray it onto the last-stage blade, forming a layer of corrosion-resistant protective coating on the blade surface that is firmly bonded to the substrate. However, the spray layer and the blade are mechanically bonded, the bonding strength is low, the coating is easy to peel off, and it cannot provide long-term protection. Alternatively, the anti-corrosion ability of the last-stage blade can be increased before it is put into use. The commonly used blade anti-corrosion process is to braze the Stellite alloy sheet at the end of the blade, which alleviates the blade water erosion to a certain extent. However, the water erosion resistance of the Stellite alloy sheet is insufficient, and water erosion will still occur after a period of service. In severe cases, the damage cracks can pass through the Stellite alloy to reach the surface of the blade substrate, causing blade damage; at the same time, affected by the brazing process, the Stellite alloy sheet is prone to fall off during service, affecting the safe operation of the steam turbine unit. Therefore, a technical means with high hardness, high toughness, fatigue resistance and water erosion resistance is urgently needed to reduce the risk of blade water erosion damage to improve the reliability of steam turbine operation. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defects in the prior art, thereby providing a repair layer for water erosion damage of a last-stage blade of a steam turbine and a preparation method thereof.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A repair layer for water erosion damage of a last-stage blade of a steam turbine is formed by laser cladding in a region to be repaired of the last-stage blade, and comprises at least one restoration layer. A first laser cladding material required for laser cladding of the restoration layer comprises 20% of a strong and tough phase and 80% of a nickel-chromium-based alloy powder. The mass percentage of each element in the nickel-chromium-based alloy powder is: C 0.03-0.08%, Cr 30.45-30.55%, Si 0.15-0.25%, Fe 8.15-8.25%, Mo 1.45-1.55% and the balance is Ni.

[0007] Further, the tough phase is WC;

[0008] The phases of the recovery layer formed by the first laser cladding material after laser cladding are NiCr solid solution, Cr 23 C 6 , Fe 6 W 6 C and WC.

[0009] Furthermore, the nickel-chromium-based alloy powder has a particle size of 40-150 μm.

[0010] Furthermore, the repair layer also includes a transition layer, which is located between the area to be repaired of the last-stage blade and the restoration layer, the lower surface of the transition layer is metallurgically bonded to the upper surface of the area to be repaired of the last-stage blade, and the upper surface of the transition layer is metallurgically bonded to the lower surface of the restoration layer.

[0011] Furthermore, the second laser cladding material required for the transition layer includes 20% strong and tough phase and 80% iron-based alloy powder;

[0012] The mass percentages of the elements in the iron-based alloy powder are: C 0.15-0.25%, Cr 17.45-17.55%, Si 1.45-1.55%, Ni 1.95-2.05% and the balance Fe.

[0013] Further, the tough phase is WC;

[0014] The phase of the transition layer formed by the second laser cladding material after laser cladding is Cr 23 C 6 , Fe 3 W 3 C.Fe 6 W 6C and WC; and / or

[0015] The particle size of the iron-based alloy powder is 40-150 μm.

[0016] Furthermore, the thickness of the transition layer is 0.8-1.0 mm.

[0017] In order to achieve the above object, the present invention also adopts the following technical solutions:

[0018] A method for preparing a repair layer for water erosion damage on a last-stage blade of a steam turbine comprises the following steps:

[0019] Step S 1 1. Perform surface pretreatment on the last-stage blade to be repaired until the surface is smooth and complete;

[0020] Step S 2 , laser cladding is performed on the area to be repaired on the pre-treated last-stage blade according to the automatically planned path to form a transition layer;

[0021] Step S 3 , performing laser cladding on the transition layer according to the automatically planned laser cladding path to form at least one recovery layer.

[0022] Furthermore, the step S 3 Specifically include:

[0023] Step S 31 , automatically plan the laser cladding path for the area to be repaired;

[0024] Step S 32 , using laser cladding equipment to laser clad a recovery layer, cooling the recovery layer after laser cladding, cleaning the surface, and performing PT inspection to determine whether it meets the standards;

[0025] If not, grind off the restored layer and return to step S. 32 , until the criteria are met;

[0026] Step S 33 , determine whether the number of laser cladding layers in the automatically planned laser cladding path is greater than the number of laser cladding layers;

[0027] If yes, return to step S 32 Perform the next layer of laser cladding until the last blade to be repaired is repaired according to the automatically planned laser cladding path;

[0028] If not, proceed to the next step;

[0029] Step S 342. Grind the outer surface of the restoration layer to restore the repaired last-stage blade to its original size, and conduct PT inspection to determine whether it meets the standards;

[0030] If not, the outermost restoration layer is removed by grinding and the process returns to step S. 32 , until the criteria are met.

[0031] Further, the parameters of the laser cladding restoration layer are: laser cladding power 1500W, scanning speed 16mm / s, spot 15mm, powder feeding speed 70g / min; and / or

[0032] The parameters for setting the transition layer of laser cladding are: laser cladding power 1500W, scanning speed 3mm / s, spot 3mm, powder feeding speed 25g / min.

[0033] In summary, compared with the prior art, the present invention has at least the following beneficial effects:

[0034] The invention relates to a repair layer for water erosion damage of a last-stage blade of a steam turbine, which is formed by laser cladding in a region to be repaired of the last-stage blade, and comprises at least one restoration layer, wherein a first laser cladding material required for laser cladding of the restoration layer comprises 20% of a strong and tough phase and 80% of a nickel-chromium-based alloy powder, wherein the mass percentage of each element in the nickel-chromium-based alloy powder is: C 0.03-0.08%, Cr 30.45-30.55%, Si 0.15-0.25%, Fe 8.15-8.25%, Mo 1.45-1.55% and the balance is Ni, wherein when laser cladding is used to prepare the restoration layer, the Cr and Fe in the nickel-chromium-based alloy powder can react with the elements produced by the high-temperature decomposition of the strong and tough phase to generate a fine hard phase, exerting a dispersion strengthening effect, and Ni and Cr can generate (Ni, Cr) solid solution under high temperature, play a solid solution strengthening effect, and precipitate carbides as nucleation centers to promote the formation of secondary dendrites, effectively refine the grains generated in the restoration layer, and play a fine grain strengthening effect. Through the combination of dispersion strengthening, solid solution strengthening and fine grain strengthening, the repair layer containing the restoration layer laser clad on the last-stage blade of the turbine has the advantages of high hardness, high toughness, good fatigue resistance and strong water erosion resistance, effectively extending the service life of the last-stage blade of the turbine and improving economic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 The present invention is a schematic diagram of the structure of a repair layer for water erosion damage on a last-stage blade of a steam turbine provided in one embodiment of the present invention.

[0037] Figure 2 This is the X-ray diffraction pattern of the transition layer in Example 1 provided by the present invention.

[0038] Figure 3 This is the X-ray diffraction pattern of the recovery layer in Example 1 provided by the present invention.

[0039] Figure 4 This is a scanning electron microscope image of the transition layer in Example 1 provided by the present invention.

[0040] Figure 5 This is a scanning electron microscope image of the recovery layer in Example 1 provided by the present invention.

[0041] Figure 6 This is a comparison chart of the hardness and impact absorption energy of the last-stage blade substrate, transition layer and recovery layer in Example 1 provided by the present invention.

[0042] Figure 7 This is a comparative analysis diagram of the fatigue resistance of the last-stage blade substrate, transition layer and restoration layer in Example 1 provided by the present invention.

[0043] Figure 8 This is a comparative analysis diagram of the water erosion resistance of the last-stage blade substrate, transition layer and restoration layer in Example 1 provided by the present invention.

[0044] Description of reference numerals:

[0045] 1. Final blades;

[0046] 2. Repair layer; 21. Transition layer; 22. Restoration layer. DETAILED DESCRIPTION

[0047] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0049] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0050] As attached Figure 1 As shown, the present invention provides a repair layer for water erosion damage of a last-stage blade of a steam turbine, which is formed by laser cladding in the area to be repaired of the last-stage blade 1, and includes at least one restoration layer 22. The first laser cladding material required for the laser cladding restoration layer 22 includes 20% strong and tough phase and 80% nickel-chromium-based alloy powder. The mass percentage of each element in the nickel-chromium-based alloy powder is: C 0.03-0.08%, Cr 30.45-30.55%, Si0.15-0.25%, Fe 8.15-8.25%, Mo 1.45-1.55% and the balance is Ni.

[0051] Specifically, when laser cladding the restoration layer 22, Cr and Fe in the nickel-chromium-based alloy powder can react with the elements produced by the high-temperature decomposition of the strong and tough phase to generate a fine hard phase, effectively playing a dispersion strengthening role; and Ni, as one of the important components of the iron-based alloy powder, Ni and Cr can generate (Ni, Cr) solid solution under high temperature, play a solid solution strengthening role, and precipitate carbides as nucleation centers to promote the formation of secondary dendrites, effectively refine the grains generated in the restoration layer 22, and play a fine grain strengthening role. After the combination of dispersion strengthening, solid solution strengthening and fine grain strengthening, the restoration layer 22 prepared by laser cladding using the first laser cladding material has the advantages of high hardness, high toughness, good fatigue resistance and strong water erosion resistance, effectively extending the service life of the turbine last stage blade 1, reducing the maintenance cost of the turbine last stage blade 1, and thereby improving the economic efficiency.

[0052] In addition, since water erosion damage may cause pits, wear and scratches of varying degrees on the surface of the last-stage blade 1 of the steam turbine, in order to better restore the shape of the last-stage blade 1, the restoration layer 22 is at least one layer. The user can adjust the thickness of the restoration layer 22 according to the setting parameters of the laser cladding device, and gradually and finely restore the area to be repaired of the last-stage blade 1 to its original shape, so as to prevent large internal stress from being generated during cooling and solidification after laser cladding, thereby generating cracks inside, and ensure the stability and reliability of the restoration layer 22. Among them, the specific number of layers needs to be determined and designed by the online laser cladding device according to the actual water erosion damage of the last-stage blade 1 of the steam turbine, and is not limited here.

[0053] In some embodiments of the present invention, the tough phase is WC, which can significantly enhance the mechanical properties and wear resistance of the first laser cladding material when it is clad into a recovery layer. Specifically, the phase of the recovery layer 22 formed by the first laser cladding material after laser cladding is NiCr solid solution, Cr 23 C 6 , Fe 6 W 6 C and WC. After high-temperature laser cladding, Cr and Fe in the Ni-Cr-based alloy powder can react with W and C produced by high-temperature decomposition of WC to generate Cr 23 C 6 , Fe 6 W 6 C and WC fine hard phases can effectively play a role of dispersion strengthening. Ni and Cr can be under high temperature, Cr enters Ni crystal to form a new face-centered cubic structure, namely (Ni, Cr) solid solution. The difference in atomic radius between the solute atom Cr and Ni will cause lattice distortion, hinder the slip between crystal layers, and make the recovery layer 22 more difficult to deform and achieve higher strength; and the distance between Cr and Ni atoms changes, and more forces need to be overcome during the displacement process, which can also play a role in making it more difficult to deform. In addition, the atoms inside the recovery layer 22 will be unevenly distributed, and defects will occur in the area where the (Ni, Cr) solid solution gathers to form stacking faults. The displaced atoms need more energy to pass through the stacking faults, thereby effectively preventing the displacement of atoms. Therefore, in summary, the solid solution strengthening effect of the (Ni, Cr) solid solution can effectively improve the strength of the recovery layer 22. Furthermore, the carbide Cr precipitated at high temperature after laser cladding 23 C 6 , Fe 6 W 6C and WC can both act as nucleation centers to promote the formation of secondary dendrites, effectively refining the grains generated in the recovery layer 22. The finer the grains, the easier it is for plastic deformation to be dispersed in more grains, making the plastic deformation more uniform, thereby reducing internal stress concentration and preventing defects from occurring inside the recovery layer 22. Furthermore, the finer the grains, the more crystal interfaces are generated, the more tortuous the grain boundaries are, and the more opportunities there are for grains to be interlaced, which is less conducive to crack initiation and development. Therefore, the tighter the grains are, the better the toughness of the recovery layer 22, the higher the impact absorption energy value, and the stronger the protection capability when the last-stage blade 1 is subjected to water erosion impact. Grain refinement can also significantly improve the dislocation engulfment and release capabilities at the grain boundaries, thereby improving the toughness of the recovery layer 22.

[0054] In some embodiments of the present invention, the particle size of the nickel-chromium-based alloy powder is 40-150 μm, preferably spherical. When the particle size of the nickel-chromium-based alloy powder is greater than 150 μm, it may cause defects such as pores or low surface flatness in the recovery layer 22, and when the particle size of the nickel-chromium-based alloy powder is less than 40 μm, it may cause powder agglomeration and thus affect the uniformity of the laser cladding transition layer 21. Therefore, the particle size of the nickel-chromium-based alloy powder needs to be controlled within 40-150 μm.

[0055] In certain embodiments of the present invention, since the mechanical properties of the recovery layer 22 have obvious advantages over the mechanical properties of the last-stage blade 1 of the turbine, in order to prevent the generation of internal stress in the area to be repaired of the last-stage blade 1 of the turbine during the laser cladding process, which may cause rupture and peeling of the recovery layer 22, the repair layer 2 also includes a transition layer 21. The transition layer 21 is located between the area to be repaired of the last-stage blade 1 and the recovery layer 22, and plays a transition role, so that the composition and performance between the recovery layer 22 and the area to be repaired of the last-stage blade 1 gradually change to form a gradient distribution, thereby avoiding performance mutations and improving the stability and reliability of the overall repair layer 2.

[0056] Furthermore, after laser cladding, the lower surface of the transition layer 21 is metallurgically bonded to the upper surface of the area to be repaired of the last-stage blade 1, and because the first laser cladding material has good toughness and extremely high wettability, the formed recovery layer 22 has extremely high wettability to the transition layer 21, and a deep metallurgical bond is formed during the laser cladding process, so the bonding method of the upper surface of the transition layer 21 and the lower surface of the recovery layer 22 is also metallurgical bonding. Compared with simple mechanical bonding, metallurgical bonding effectively enhances the connection strength, and the transition layer 21 and the area to be repaired of the last-stage blade 1 and the recovery layer 22 are not easy to peel off, so that the repair layer 2 can be tightly bonded to the area to be repaired of the last-stage blade 1.

[0057] In certain embodiments of the present invention, since the main components of the preparation material of the turbine last-stage blade 1 generally include Cr, Ni, Si and a large amount of iron, in order to make it easier for the transition layer 21 to form a metallurgical bond with the area to be repaired of the last-stage blade 1 and prevent cracking during laser cladding, the composition of the second laser cladding material required for the laser cladding transition layer 21 is selected from a material containing an iron-based alloy powder and having good compatibility with the last-stage blade 1 so that the physical properties such as the thermal expansion coefficient are gradually transitioned. Therefore, the second laser cladding material required for the transition layer 21 includes 20% strong and tough phase and 80% iron-based alloy powder; the mass percentage of each element in the iron-based alloy powder is: C0.15-0.25%, Cr 17.45-17.55%, Si 1.45-1.55%, Ni 1.95-2.05% and the balance is Fe. Among them, the main components of the iron-based alloy powder are similar to the main components of the last-stage blade 1 of the steam turbine, and are also similar to the main components of the nickel-chromium-based alloy powder, which avoids cracking during the laser cladding process and plays a role of gradual transition. The Fe, Cr and W elements in the second laser cladding material can combine with C in the area to be repaired of the last-stage blade 1 to form a carbide hard phase. The Ni element can improve the toughness of the transition layer 21 and reduce its tendency to crack. The Si element preferentially combines with oxygen during the laser cladding process to form a glassy oxide on the surface of the molten pool, which prevents the oxidation of the liquid metal below, and can also improve the wettability between the molten pool and the substrate of the last-stage blade 1. Therefore, the transition layer 21 prepared by the second laser cladding material can not only form a good metallurgical bond with the area to be repaired of the last-stage blade 1, but also realize the gradual transition of the substrate of the last-stage blade 1, the transition layer 21 and the recovery layer 22.

[0058] Specifically, in some embodiments of the present invention, the tough phase is WC, and the phase of the transition layer 21 formed by the second laser cladding material after laser cladding is Cr. 23 C 6 , Fe 3 W 3 C.Fe 6 W 6 C and WC.

[0059] Among them, similar to the nickel-chromium-based alloy powder, after high-temperature laser cladding, the Cr and Fe in the iron-based alloy powder can react with the W and C produced by the high-temperature decomposition of WC to generate Cr 23 C 6 , Fe 6 W 6 C.Fe 3 W 3 C, and WC fine hard phases effectively play a role in dispersion strengthening. Furthermore, the carbide Cr precipitated at high temperature after laser cladding 23 C 6 , Fe 3 W3 C.Fe 6 W 6 C and WC can both act as nucleation centers to promote the formation of secondary dendrites, effectively refining the grains generated in the transition layer 21. The finer the grains, the easier it is for plastic deformation to be dispersed in more grains, making the plastic deformation more uniform, thereby reducing internal stress concentration and preventing defects from occurring inside the transition layer 21. Furthermore, the finer the grains, the more crystal interfaces are generated, the more tortuous the grain boundaries are, and the more opportunities there are for grains to be interlaced, which is less conducive to crack initiation and development. Therefore, the tighter the grains are, the better the toughness of the transition layer 21, and the higher the impact absorption energy value, the less impact force is transferred to the last-stage blade 1 when the last-stage blade 1 is subjected to water erosion impact, thereby effectively protecting the last-stage blade 1. Grain refinement can also significantly improve the dislocation engulfment and release capabilities at the grain boundaries, thereby improving the toughness of the transition layer 21.

[0060] In some embodiments of the present invention, the particle size of the iron-based alloy powder is 40-150 μm, preferably spherical. Similar to the laser cladding of nickel-chromium-based alloy powder, when the particle size of the iron-based alloy powder is greater than 150 μm, it may cause defects such as pores or low surface flatness in the transition layer 21, and when the particle size of the iron-based alloy powder is less than 40 μm, it may cause powder agglomeration and affect the uniformity of the laser cladding transition layer 21. Therefore, the particle size of the nickel-chromium-based alloy powder needs to be controlled at 40-150 μm.

[0061] In some embodiments of the present invention, the thickness of the transition layer 21 is 0.8-1.0 mm, preferably 0.8 mm.

[0062] In addition to the above-mentioned repair layer for water erosion damage of the last stage blade of the steam turbine, the present invention also provides a method for preparing the repair layer for water erosion damage of the last stage blade of the steam turbine. The preparation method of the repair layer for water erosion damage of the last stage blade of the steam turbine and the above-mentioned repair layer for water erosion damage of the last stage blade of the steam turbine can correspond to each other.

[0063] A method for preparing a repair layer for water erosion damage of a last-stage blade of a steam turbine comprises the following steps:

[0064] Step S 1 , pre-treat the surface of the last-stage blade to be repaired until the surface is smooth and complete.

[0065] Specifically, the pretreatment method can be selected to use the corresponding cleaning agent to wipe the last stage blades of the turbine, use an angle grinder to grind the last stage blades of the turbine, use sandblasting to clean, etc., until the surface of the last stage blades is smooth and complete, so that it is easier to improve the metallurgical bonding strength with the transition layer later. In addition, to determine whether the last stage blades are smooth and complete after pretreatment, you can use the naked eye to identify or use PT inspection and other methods to ensure that there are no defects on the surface. It is worth noting that the pretreatment method and the judgment criteria after the pretreatment are selected and adjusted in combination with the actual application of the last stage blades of the turbine, product requirements and quality requirements, and are not limited here.

[0066] Step S 2 2. Perform laser cladding on the repaired area on the pre-treated last-stage blade according to the automatically planned path to form a transition layer. After the transition layer cools, clean the surface and perform PT inspection to determine whether it meets the NB / T47013.5 non-destructive testing of pressure equipment, part 5, penetration testing standard level I (qualified);

[0067] If not, grind off the transition layer and return to laser clad the transition layer again until the standard is met.

[0068] Furthermore, the parameters of the laser cladding transition layer setting are: laser cladding power 1500W, scanning speed 3mm / s, spot size 3mm, and powder feeding speed 25g / min.

[0069] Step S 3 , performing laser cladding on the transition layer according to the automatically planned laser cladding path to form at least one recovery layer.

[0070] Specifically, step S 3 The following steps are involved:

[0071] Step S 31 , automatically plan the laser cladding path for the area to be repaired;

[0072] Step S 32 1. Use laser cladding equipment to laser clad a recovery layer, cool the recovery layer after laser cladding, clean the surface, and perform PT inspection to determine whether it meets the NB / T47013.5 non-destructive testing of pressure equipment, part 5, penetration testing standard level I (qualified);

[0073] If not, grind off the restored layer and return to step S. 32 , until it meets the NB / T47013.5 non-destructive testing of pressure equipment, part 5, penetration testing standard, level I (qualified);

[0074] Step S 33 , determine whether the number of laser cladding layers in the automatically planned laser cladding path is greater than the number of laser cladding layers;

[0075] If yes, return to step S 32 Perform the next layer of laser cladding until the last blade to be repaired is repaired according to the automatically planned laser cladding path;

[0076] If not, proceed to the next step;

[0077] Step S 34 2. Grind the outer surface of the restoration layer to restore the repaired last-stage blade to its original size, and conduct PT inspection to determine whether it meets the NB / T47013.5 non-destructive testing of pressure equipment, part 5, penetration testing standard, level I (qualified);

[0078] If not, the outermost restoration layer is removed by grinding and the process returns to step S. 32 , until the criteria are met.

[0079] It is worth mentioning that each recovery layer clad by laser cladding must be PT inspected to meet quality requirements, so that defects occurring during the laser cladding process can be discovered in the preparation stage, preventing poor bonding problems due to defects during the subsequent cladding of the recovery layer or failures during the use of the repaired last-stage blade, leading to safety accidents and economic losses.

[0080] Furthermore, the parameters of the laser cladding restoration layer are: laser cladding power 1500W, scanning speed 16mm / s, spot 15mm, powder feeding speed 70g / min. Compared with the setting parameters of the transition layer, the scanning speed, spot and powder feeding speed are all improved, which is conducive to the formation of Fe with more Fe and C in the powder and better stability. 6 W 6 C physical phase.

[0081] In order to further illustrate the technical solution of the present invention, the preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0082] Example 1

[0083] Step S 1 1. Use sandblasting to pre-treat the surface of the last-stage blade to be repaired until the surface is smooth and complete when observed with the naked eye;

[0084] Step S 2, laser cladding is performed on the repaired area on the pretreated last-stage blade according to the automatically planned path. The laser cladding parameters are as follows: laser cladding power 1500W, scanning speed 3mm / s, spot 3mm, powder feeding speed 25g / min, and the cladding materials used for laser cladding include 20% WC and 80% iron-based alloy powder composed of 0.2% C, 17.5% Cr, 1.5% Si, 2.0% Ni and 78.8% Fe. After forming a 0.8mm transition layer and waiting for the transition layer to cool, the surface is cleaned and PT inspection is performed to determine that it meets the NB / T47013.5 non-destructive testing of pressure equipment, part 5, penetration testing standard level I (qualified);

[0085] Step S 31 , automatically plan the laser cladding path for the area to be repaired, with two restoration layers;

[0086] Step S 32 1. A laser cladding device is used to laser clad a layer of recovery layer. The laser cladding parameters are as follows: laser cladding power 1500W, scanning speed 16mm / s, spot 15mm, powder feeding speed 70g / min. The cladding materials used for laser cladding include 20% WC and 80% nickel-chromium-based alloy powder composed of 0.03% C, 30.5% Cr, 0.2% Si, 8.2% Fe, 1.5% Mo and 59.57% Ni. After forming a layer of recovery layer, the recovery layer is cooled, the surface is cleaned, and PT inspection is performed to determine that it meets the NB / T47013.5 non-destructive testing of pressure equipment, part 5, penetration testing standard level I (qualified);

[0087] Step S 33 1. Determine that the number of laser cladding layers (2 layers) in the automatically planned laser cladding path is greater than the number of laser cladding layers (1 layer); continue to use laser cladding equipment to laser clad a recovery layer, cool the recovery layer after laser cladding, clean the surface, and perform PT inspection to determine that it meets the NB / T47013.5 non-destructive testing of pressure equipment, part 5, penetration testing standard level I (qualified); determine that the number of laser cladding layers (2 layers) in the automatically planned laser cladding path is not greater than the number of laser cladding layers (2 layers);

[0088] Step S 34 , polish the outer surface of the restoration layer to restore the repaired last-stage blade to its original size, and conduct PT inspection to determine whether it meets the NB / T47013.5 Nondestructive Testing of Pressure Equipment Part 5 Penetration Testing Standard Level I (qualified).

[0089] The base, transition layer and restoration layer of the last blade in Example 1 were tested, and the specific test results were analyzed as follows:

[0090] (1) XRD analysis: Figure 2As shown in the figure, during the laser cladding process of the transition layer, the WC particles decompose into W and C at high temperature, and react chemically with the alloy elements Cr and Fe. The precipitated phase is Cr 23 C 6 , Fe 6 W 6 C.Fe 3 W 3 C, and WC carbide hard phases, Figure 3 As shown in the figure, during the laser cladding process of the recovery layer, WC particles decompose into W and C at high temperature, and the precipitated phases are NiCr solid solution and Cr 23 C 6 , Fe 6 W 6 Based on the phase analysis results, it can be seen that on the one hand, carbides are precipitated in both the transition layer and the restoration layer as nucleation centers, which promote the formation of secondary dendrites, refine the grains of the cladding layer, play a role in fine grain strengthening, and combined with the dispersion strengthening effect of each hard phase, the performance of the final repair layer can be effectively improved; on the other hand, the phase of the restoration layer is less than that of the transition layer. 3 W 3 C and more NiCr solid solution, while Fe 6 W 6 C compared to Fe 3 W 3 C has better stability. Due to the adjustment of laser cladding parameters and the difference of laser cladding materials, more Fe and C in the transition layer generate Fe 6 W 6 C, Fe 3 W 3 C is not generated or the amount generated is so small that it cannot be detected by XRD, and the NiCr solid solution in the recovery layer has a good solid solution strengthening effect. Therefore, in summary, the performance of the recovery layer is significantly better than that of the transition layer. Finally, in the repair layer obtained by laser cladding of the last-stage blade, the energy of the last-stage blade, the transition layer and the repair layer is gradually enhanced, which can achieve good metallurgical bonding and protect the last-stage blade.

[0091] (2) Microstructure analysis: as shown in the attached Figure 4-5As shown in the figure, the transition layer and the recovery layer promote the formation of secondary dendrites due to the carbides precipitated at high temperature after laser cladding as nucleation centers, and the generated grain size does not exceed 5μm. The grains are effectively refined, and the grains of the recovery layer are significantly smaller than the grain size of the transition layer, which can produce better fine grain strengthening. Furthermore, several types of carbide hard phase particles play a skeleton role in the transition layer and the recovery layer, which strengthens the bearing capacity of the transition layer and the recovery layer. The melting of powder particles is conducive to the solid solution strengthening of the transition layer and the recovery layer. The carbides precipitated in the transition layer and the recovery layer during the laser cladding re-solidification process play a fine grain strengthening role on the coating tissue dendrites. The spherical laser cladding powder has good fluidity, is fully dissolved and more evenly distributed in the transition layer and the recovery layer, resulting in the plastic properties of the transition layer and the recovery layer, which can resist impact, jet extrusion and diffusion shear. The effect of toughness on water erosion is mainly reflected in the fact that the high-toughness transition layer and the recovery layer materials can better resist the erosion of water droplets and reduce the surface damage of the transition layer and the recovery layer. When impacted, the high-toughness transition layer and the recovery layer can absorb energy through plastic deformation, thereby reducing the generation and expansion of cracks, which makes the erosion of water droplets on the high-toughness transition layer and the recovery layer relatively small. In particular, the structure of the recovery layer is dense and fine, with the highest hardness and toughness. A large amount of hard phase is dispersed on the surface of the recovery layer, which can resist the destructive effect of softened water and play a significant protective role.

[0092] (3) Hardness and impact absorption energy analysis: Figure 6 As shown in the figure, the hardness and impact absorption energy of the recovery layer are stronger than those of the transition layer, and the hardness and impact absorption energy of the transition layer are significantly stronger than those of the last-stage blade substrate. The repair layer composed of the transition layer and the recovery layer has good toughness and hardness. This is because the grains in the transition layer and the recovery layer are finer. The finer the grains, the more crystal interfaces are produced, the more tortuous the grain boundaries are, and the more opportunities there are for the grains to be interlaced, which is less conducive to the initiation and development of cracks. Therefore, the tighter the grains are, the better the toughness is, and the higher the impact absorption energy value is, the stronger the protection ability of the repair layer when the last-stage blade is impacted by water erosion. In addition, grain refinement can also lead to a significant increase in the ability to engulf and release dislocations at the grain boundaries, thereby improving the toughness of the repair layer.

[0093] (4) Anti-fatigue performance analysis: Figure 7 As shown in Figure 2, the number of cycles of the last blade substrate, transition layer, and recovery layer is 5.4×10 5 , 5.09×10 6 and 5.16×10 6 This shows that the fatigue resistance of the restoration layer is better than that of the transition layer, and the fatigue resistance of both is also significantly better than that of the last-stage blade substrate. Therefore, the repair layer composed of the transition layer and the restoration layer can effectively extend the service life of the last-stage blade of the turbine.

[0094] (5) Water erosion resistance analysis: Figure 8 As shown in the figure, the erosion weight loss of the last-stage blade substrate, transition layer and restoration layer are 0.489g, 0.145g and 0.115g respectively, indicating that the erosion resistance of the transition layer and the restoration layer under water droplet erosion is better than that of the last-stage blade substrate, and the erosion resistance of the restoration layer is better than that of the transition layer. Therefore, laser cladding of the repair layer composed of the transition layer and the restoration layer on the last-stage blade can make the last-stage blade have better erosion resistance.

[0095] In summary, based on the analysis of the results of each test, the repair layer composed of the transition layer and the recovery layer has the advantages of high hardness, high toughness, good fatigue resistance and strong water erosion resistance. Laser cladding on the last-stage blades of the steam turbine can effectively extend the service life of the last-stage blades of the steam turbine and reduce the number of subsequent maintenance of the last-stage blades, thereby improving the economy.

[0096] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A repair layer for water erosion damage of a last-stage blade of a steam turbine, characterized in that: The area to be repaired of the last-stage blade is formed by laser cladding, including at least one restoration layer. The first laser cladding material required for laser cladding of the restoration layer includes 20% strong and tough phase and 80% nickel-chromium-based alloy powder. The mass percentage of each element in the nickel-chromium-based alloy powder is: C 0.03-0.08%, Cr 30.45-30.55%, Si 0.15-0.25%, Fe8.15-8.25%, Mo 1.45-1.55% and the balance is Ni.

2. The repair layer for water erosion damage of the last stage blade of a steam turbine according to claim 1, characterized in that: The tough phase is WC; The phases of the recovery layer formed by the first laser cladding material after laser cladding are NiCr solid solution, Cr 23 C6, Fe6W6C and WC.

3. The repair layer for water erosion damage of the last stage blade of a steam turbine according to claim 1, characterized in that: The particle size of the nickel-chromium-based alloy powder is 40-150 μm.

4. The repair layer for water erosion damage of the last stage blade of a steam turbine according to claim 1, characterized in that: The repair layer also includes a transition layer, which is located between the area to be repaired of the last-stage blade and the restoration layer. The lower surface of the transition layer is metallurgically bonded to the upper surface of the area to be repaired of the last-stage blade, and the upper surface of the transition layer is metallurgically bonded to the lower surface of the restoration layer.

5. The repair layer for water erosion damage of the last stage blade of a steam turbine according to claim 4, characterized in that: The second laser cladding material required for the transition layer includes 20% strong and tough phase and 80% iron-based alloy powder; The mass percentages of the elements in the iron-based alloy powder are: C 0.15-0.25%, Cr 17.45-17.55%, Si 1.45-1.55%, Ni 1.95-2.05% and the balance Fe.

6. The repair layer for water erosion damage of the last stage blade of a steam turbine according to claim 5, characterized in that: The tough phase is WC; the phase of the transition layer formed by the second laser cladding material after laser cladding is Cr 23 C6, Fe3W3C, Fe6W6C and WC; and / or The particle size of the iron-based alloy powder is 40-150 μm.

7. The repair layer for water erosion damage of the last stage blade of a steam turbine according to claim 4, characterized in that: The thickness of the transition layer is 0.8-1.0 mm.

8. A method for preparing a repair layer for water erosion damage on a last-stage blade of a steam turbine according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step S1, pre-treating the surface of the last-stage blade to be repaired until the surface is smooth and complete; Step S2, performing laser cladding on the area to be repaired on the pre-treated last-stage blade according to the automatically planned path to form a transition layer; Step S3: performing laser cladding on the transition layer according to the automatically planned laser cladding path to form at least one restoration layer.

9. The method for preparing a repair layer for water erosion damage of a last-stage blade of a steam turbine according to claim 8, characterized in that: The step S3 specifically includes: Step S 31 , automatically plan the laser cladding path for the area to be repaired; Step S 32 , using laser cladding equipment to laser clad a recovery layer, cooling the recovery layer after laser cladding, cleaning the surface, and performing PT inspection to determine whether it meets the standards; If not, grind off the restored layer and return to step S. 32 , until the criteria are met; Step S 33 , determine whether the number of laser cladding layers in the automatically planned laser cladding path is greater than the number of laser cladding layers; If yes, return to step S 32 Perform the next layer of laser cladding until the last blade to be repaired is repaired according to the automatically planned laser cladding path; If not, proceed to the next step; Step S 34 2. Grind the outer surface of the restoration layer to restore the repaired last-stage blade to its original size, and conduct PT inspection to determine whether it meets the standards; If not, the outermost restoration layer is removed by grinding and the process returns to step S. 32 , until the criteria are met.

10. The method for preparing a repair layer for water erosion damage of a last-stage blade of a steam turbine according to claim 8, characterized in that: The parameters of the laser cladding restoration layer are: laser cladding power 1500W, scanning speed 16mm / s, spot 15mm, powder feeding speed 70g / min; and / or The parameters for setting the transition layer of laser cladding are: laser cladding power 1500W, scanning speed 3mm / s, spot 3mm, powder feeding speed 25g / min.